2011
DOI: 10.1037/a0024625
|View full text |Cite
|
Sign up to set email alerts
|

The latent structure of Multiphasic Sex Inventory–Assessed Pedophilic Interest.

Abstract: The Multiphasic Sex Inventory (MSI; Nichols & Molinder, 1984) is a self-report measure frequently used in the assessment of sex offenders. Scores on the MSI are often used to assess levels of pedophilic interest. However, the question of whether men with pedophilia represent a unique group distinguished by their sexual interests, or whether they are high-scorers on a continuum of sexual interest in children among men who sexually offend against children remains unanswered. Because no existing evidence points c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
2
15
0
1
Order By: Relevance
“…On the other hand, Mackaronis, Strassberg, and Marcus (2011) reported that sexual interest in children as measured with the self-report Multiphasic Sex Inventory (MSI; Nichols & Molinder, 1996) was found to be a dimensional, not a taxonic construct.…”
Section: Is Pedophilic Sexual Preference Continuous? a Taxometric Anamentioning
confidence: 99%
“…On the other hand, Mackaronis, Strassberg, and Marcus (2011) reported that sexual interest in children as measured with the self-report Multiphasic Sex Inventory (MSI; Nichols & Molinder, 1996) was found to be a dimensional, not a taxonic construct.…”
Section: Is Pedophilic Sexual Preference Continuous? a Taxometric Anamentioning
confidence: 99%
“…Bei einer nicht-exklusiven Pädophilie kann sich der Betroffene hingegen auch zu Erwachsenen sexuell hingezogen fühlen (APA 2013). Das Ausmaß des sexuellen Interesses an Kindern ist individuell unterschiedlich, sodass Pädophilie auch als dimensionales Konstrukt mit unterschiedlichen Ausprägungsgraden verstanden werden kann (Mackaronis et al 2011;Stephens et al 2017).…”
Section: Unter Pädophilie Versteht Man Ein Intensives Und Anhaltendesunclassified
“…It should be noted that several studies have sought to determine whether the latent structure of pedophilic disorder is taxonic (patients with pedophilic disorders represent a discrete class of individuals) or dimensional (sexual interest in children is best conceptualized as a continuum). No definitive conclusion has been reached, with studies supporting a dimensional structure (Mackaronis, Strassberg, & Marcus, 2011; Stephens, Leroux, Skilling, Cantor, & Seto, 2017) or a taxonic one (McPhail, Olver, Brouillette-Alarie, & Looman, 2018; Schmidt, Mokros, & Banse, 2013). In the present study, we assumed that within the population of men with pedophilia, sexual interest for children varied across patients or even within patients.…”
Section: Introductionmentioning
confidence: 99%